Coupling CoFe2O4 and SnS2 nanoparticles with reduced graphene oxide as a high-performance electromagnetic wave absorber. Issue 14 (1st November 2016) - Zhang, Na; Huang, Ying; Zong, Meng; Ding, Xiao; Li, Suping; Wang, Mingyue
Abstract: The reduced graphene oxide (RGO)/CoFe2 O4 /SnS2 composites have been successfully synthesized by two-step hydrothermal processes. TEM results show that CoFe2 O4 and SnS2 nanoparticles with both diameters about 5–10 nm are well dispersed on the surface of graphene. Compared with RGO/CoFe2 O4 composites, the as-prepared RGO/CoFe2 O4 /SnS2 composites exhibit excellent electromagnetic (EM) wave absorption properties in terms of both the maximum reflection loss and the absorption bandwidth. The maximum reflection loss of RGO/CoFe2 O4 /SnS2 composites is −54.4 dB at 16.5 GHz with thickness of only 1.6 mm and the absorption bandwidth with the reflection loss below −10 dB is up to 12.0 GHz (from 6.0 to 18.0 GHz) with a thickness in the range of 1.5–4.0 mm. And especially, they cover the whole X band (8.0–12.0 GHz), which could be used for military radar and direct broadcast satellite (DBS).